Proposed Business Strategy for Dollies using Diamond Strategy Framework - Hambali, Sofyana; Toha, Moh (The Indonesian Journal of Business Administration, 2015)
Abstract. Dollies is one of online store that established since 2010 and engaged in Fashion industry. Dollies main product is a clothes that specialize for young women. Technology and information growth made online business growing fast and led to a high level of competition. Competition also comes from offline store, local brands and famous brand that now begin to explore online and offline media in Indonesia. Dollies main problem are the high number of competitors and decreasing number of sales periodically. The main purpose of this research is to determine appropriate strategy for Dollies. Steps to determine strategy consist of defining new arena, formulate Dollies differentiators, formulate the staging to win the competition, select vehicle, and evaluate the economic logic of the business to winning the competition.The research begin with analyzing the external and internal business situation. External analysis conducted using PESTEL analysis, Porter Five Forces, and Strategy Three C’s. From external analysis found that fashion business is still potential along with the economic growth but the environment is a heavy arena because the pressure came from many aspect. Internal analysis conducted by using Value Chain Analysis, it revealed that Dollies have very simple organizational and operational structure. Besides that, Dollies lack in capital, human resource, and promotion. External and Internal business then will formulate in SWOT analysis. SWOT analysis used to define an appropriate generic strategy for Dollies. After analyze using SWOT analysis, revealed that Integration Strategy is the most suitable for Dollies. Integration strategy is a combination of cost leadership and differentiation. Arena is defined by analyzing arena alternatives using SWOT. Differentiation is defined by doing research to customer. Research conduct through interview that and questionnaire. The purpose of interview is to know what factor that important while doing online shopping using saturated method, where respondent will asked until there is no new answer revealed. From interview section, there are 12 important factors based on customer experience: quality, (low) price, product visual, fast respond, good service, customer testimony, promo discount, limited stock, fast shipment, product detail, ease of payment, and followers number. Based on questionnaire result, there are 7 key success factor in online shopping based on customer perspective. The key success factor result are service, price, fast shipping, fast respond, quality, ease of payment, and discount. Key success factor determine differentiation of Dollies, where the differentiation of Dollies are providing good service, quality, ease of payment and affordable price at the same time, provide fastness of online shopping, and provide update model ( new collection every 4 day).The research presented in a diamond strategy consist of several strategy: (1) choose two arena as a new arena of the business, (2) setting differentiation based on key success factors, (3) implement the differentiation into three staging, (4) analyze capital requirement for adding investment from investor, and (5) analyze the economic logic of the business. Based on questionnaire analysis and key success factor, there are significant change in business, especially in arena and differentiation. Those change then implemented into proposed business model and implementation plan.Keyword: fashion industry, business strategy, diamond strategy